Effect of Structural Configurations on Mechanical and Shape Recovery Properties of NiTi Triply Periodic Minimal Surface Porous Structures - Shuaishuai Wei; Bo Song; Lei Zhang; Xiaobo Wang; Junxiang Fan; Zhi Zhang; Yusheng Shi (Chinese Journal of Mechanical Engineering)
Abstract Based on the advantages of triply periodic minimal surface (TPMS) porous structures, extensive research on NiTi shape memory alloy TPMS scaffolds has been conducted. However, the current reports about TPMS porous structures highly rely on the implicit equation, which limited the design flexibility. In this work, novel shell-based TPMS structures were designed and fabricated by laser powder bed fusion. The comparisons of manufacturability, mechanical properties, and shape recovery responses between traditional solid-based and novel shell-based TPMS structures were evaluated. Results indicated that the shell-based TPMS porous structures possessed larger Young’s moduli and higher compressive strengths. Specifically, Diamond shell structure possessed the highest Young’s moduli of 605.8±24.5 MPa, while Gyroid shell structure possessed the highest compressive strength of 43.90±3.32 MPa. In addition, because of the larger specific surface area, higher critical stress to induce martensite transformation, and lower austenite finish temperature, the Diamond shell porous structure exhibited much higher shape recovery performance (only 0.1% residual strain left at pre-strains of 6%) than other porous structures. These results substantially uncover the effects of structural topology on the mechanical properties and shape recovery responses of NiTi shape memory alloy scaffolds, and confirm the effectiveness of this novel structural design method. This research can provide guidance for the structural design application of NiTi porous scaffolds in bone implants.